Analisis Kompetensi Manajerial Kepala Sekolah Di SMTK Pelita Nauli Sorkam Barat - Masrany Banjarnahor; Binur Panjaitan; Justice Panggabean (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine and describe the managerial competency analysis of school principals at SMTK Pelita Nauli Sorkam Barat. This research uses a qualitative approach with data collection techniques through observation, interviews and documentation. The research results show that the managerial competence of school principals has been implemented through short, medium and long term program planning, although it is not fully data-based. Organizational development is carried out through division of tasks and structuring, although there are still duplicate tasks. School leadership is carried out through directing and mobilizing the school community, but resource utilization is still not optimal. Change management is carried out through program evaluation and improvement, but facilities are still constrained. The school culture and climate have been built in a conducive manner, through instilling the values ​​of discipline, religion and cooperation. Teacher and staff management is carried out through coaching, but professional development is still limited. Facilities and infrastructure have been managed through data collection and maintenance, but are not yet optimal due to limited funds. Relations with the community have been established, but there are still obstacles. Student management is carried out from accepting new students and providing simple coaching. The curriculum refers to national policy, but specific curriculum development has not been carried out due to limited facilities. Financial management is carried out administratively, although there are still obstacles. Administrative management is carried out manually and is not yet optimal. There is no special service unit yet. Information system management has not run optimally due to limited facilities. The use of information technology is still limited. Monitoring and evaluation have been carried out, but have not been systematic and sustainable so they need to be improved.